2007
DOI: 10.1002/uog.4088
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral artery blood flow velocities and pulsatility index and the cerebroplacental pulsatility ratio: longitudinal reference ranges and terms for serial measurements

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
260
7
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(305 citation statements)
references
References 47 publications
36
260
7
2
Order By: Relevance
“…Kurmanavicius J et al 12 in a cross sectional study involving 331 normal pregnancies between 19-40 weeks also showed that MCA-PSV increases with increasing period of gestation and the 5 th percentile of both the studies were similar however the 50 th and 95 th of our study were higher than the study conducted by Kurmanavicius J et al Ebbing et al 10 in a study with 161 singleton pregnancies between 19-40 weeks period of gestation also showed that the MCA-PSV increases with increasing gestational age but the reference values were lower than this study. Tongsong et al 11 in a prospective cross-sectional descriptive study in which low-risk singleton pregnancies with accurate gestational age were recruited into the study showed a continuous increase in MCA-PSV over the period from 11-22 weeks.…”
Section: Discussionsupporting
confidence: 60%
“…Kurmanavicius J et al 12 in a cross sectional study involving 331 normal pregnancies between 19-40 weeks also showed that MCA-PSV increases with increasing period of gestation and the 5 th percentile of both the studies were similar however the 50 th and 95 th of our study were higher than the study conducted by Kurmanavicius J et al Ebbing et al 10 in a study with 161 singleton pregnancies between 19-40 weeks period of gestation also showed that the MCA-PSV increases with increasing gestational age but the reference values were lower than this study. Tongsong et al 11 in a prospective cross-sectional descriptive study in which low-risk singleton pregnancies with accurate gestational age were recruited into the study showed a continuous increase in MCA-PSV over the period from 11-22 weeks.…”
Section: Discussionsupporting
confidence: 60%
“…However, in normal fetuses, CPR normally falls after 34 weeks of gestation [66,69]. It is conceivable that the rate and/or magnitude of this fall might be greater in at risk fetuses.…”
Section: Fetal Dopplermentioning
confidence: 99%
“…This result is similar to that obtained by C. Ebbing et al, 2007, from a longitudinal study involving 161 singleton pregnancies. 30 However, our reference values had narrow range as compared to theirs probably due to small sample size and the cross sectional design of our study.Significant correlation of S: D ratio with period of gestation (r = -0.562, p <0.0001) was obtained in our study. This finding is similar to the result obtained by Justin C. Konje et al, 2005 from a prospective longitudinal study of 70 women.…”
mentioning
confidence: 55%